Genetic Methods to Identify and Manipulate Newly Born Neurons in the Adult Brain - Imayoshi, Itaru; Sakamoto, Masayuki; Kageyama, Ryoichiro (Frontiers in Neuroscience, 2011)
Although mammalian neurogenesis is mostly completed by the perinatal period, new neurons are continuously generated in the subventricular zone of the lateral ventricle and the subgranular zone of the hippocampal dentate gyrus. Since the discovery of adult neurogenesis, many extensive studies have been performed on various aspects of adult neurogenesis, including proliferation and fate-specification of adult neural stem cells, and the migration, maturation and synaptic integration of newly born neurons. Furthermore, recent research has shed light on the intensive contribution of adult neurogenesis to olfactory-related and hippocampus-mediated brain functions. The field of adult neurogenesis progressed tremendously thanks to technical advances that facilitate the identification and selective manipulation of newly born neurons among billions of pre-existing neurons in the adult central nervous system. In this review, we introduce recent advances in the methodologies for visualizing newly generated neurons and manipulating neurogenesis in the adult brain. Particularly, the application of site-specific recombinases and Tet inducible system in combination with transgenic or gene targeting strategy is discussed in further detail.